Analisis Keterkaitan Profesi, Profesional, Profesionalitas Profesionalisme dalam Meningkatkan Kompetensi Profesional Guru di Era Society 5.0 - Fista Harly; Husniah Wahyuni; Rully Hidayatullah; Hadeli Hadeli (Badan Penerbit STIEPARI Press, 2025)
The Society 5.0 era requires teachers to not only master technical competencies but also be able to integrate ethical values, empathy, and innovation in learning practices. This study aims to analyze in depth the relationship between the four concepts and their relevance to the demands of the teaching profession in the modern era that is all connected. The research method used is library research, namely by collecting data and information from various secondary sources such as scientific journals, books, articles, and relevant documents. The results of the study show that the teaching profession in the Society 5.0 era is not only required to have technical (professional) competencies, but must also reflect a strong attitude of professionalism and professionalism in facing the challenges of digital transformation. Professionalism includes the ability of teachers to continue to learn, adapt, and innovate, while professionalism reflects moral and ethical integrity in carrying out their duties. In conclusion, the relationship between the four concepts is an important foundation for teachers to remain relevant and effective in responding to educational needs in the Society 5.0 era, where technology and humanism must complement each other.